(untitled) (Journal of Philosophy Culture and Political Science, 2026)
Contemporary philosophy is experiencing a period of methodological and ideological pluralism, where traditional notions of truth are being reconsidered. A single, universal model of knowledge is being replaced by a diversity of rationalities and research approaches. In this context, addressing the humanistic aspect of truth becomes particularly important, as it implies a connection between knowledge and human experience, values, and practices. The aim of this research is to provide a philosophical understanding of methodological pluralism as the primary concept of truth in our time, to examine its humanistic potential, and to identify the connections between a variety of methodological approaches and an anthropocentric understanding of truth. This research encompasses key areas of analysis, such as the study of alethic pluralism as a contemporary approach to understanding truth, an exploration of the pragmatic perspective in the philosophy of truth, and an analysis of the impact of pluralistic approaches on the development of humanistic values ​​in science and culture. The authors emphasize the specific meaning of the word "truth," in particular, its centrality, while simultaneously affirming the dependence of truth on the world. The significance of this study lies in its contribution to the development of contemporary philosophy of science and epistemology, deepening our understanding of the relationship between truth, humanism, and the methodology of knowledge. It presents a conceptual model integrating pluralistic and pragmatic approaches to truth, allowing us to interpret truth as a dynamic, contextual, and anthropocentric category. Keywords: pluralism, philosophy, alethic pluralism, truth, modernity.